Construction of a CRIPR vector for inducing TYR gene mutations in anemonefish Amphiprion ocellaris - Nguyen, Thi Hai Thanh; Quy, Khang; Dao, Thi Mai Lan (Vietnam Journal of Biotechnology, 2025)
The anemonefish Amphiprion ocellaris is highly popular in the ornamental fish trade due to its distinctive coloration, which features a combination of orange, black, and white. The formation of black pigmentation in teleost fish is controlled by the tyrosinase-producing gene (tyr), which is responsible for melanin production. Studies have indicated that deletion mutations in the tyr gene family in fish and many other vertebrates lead to skin color abnormalities, such as albinism. The clustered regularly interspaced short palindromic repeat (CRISPR) system has emerged as a powerful and precise tool for gene editing with diverse applications. In this study, we construct a CRISPR/Cas9 system targeting the exon 2 region of the tyr gene in A. ocellaris. A guide RNA (gRNA) was designed and incorporated into the gRNA cloning vector and was subsequently introduced into Escherichia coli strain DH5-α. Afterward, the successfully incorporated gRNA sequence was validated via Sanger sequencing. The E. coli DH5-α strains carrying this recombinant plasmid were subsequently checked and screened for stability via generations. This gRNA vector together with the Cas9 plasmid will be used to generate knock-out mutations, enabling further investigation of the function of the tyr gene in melanin formation in anemonefish A. ocellaris.